2006
DOI: 10.1074/jbc.m601901200
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-HIV-1 Editing Enzyme APOBEC3G Binds HIV-1 RNA and Messenger RNAs That Shuttle between Polysomes and Stress Granules

Abstract: Deoxycytidine deaminases APOBEC3G (A3G) and APOBEC3F (A3F) (members of the apolipoprotein B mRNA-editing catalytic polypeptide 3 family) have RNA-binding motifs, invade assembling human immunodeficiency virus (HIV-1), and hypermutate reverse transcripts. Antagonistically, HIV-1 viral infectivity factor degrades these enzymes. A3G is enzymatically inhibited by binding RNA within an unidentified large cytosolic ribonucleoprotein, implying that RNA degradation during reverse transcription may activate intravirion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
205
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(235 citation statements)
references
References 76 publications
24
205
5
1
Order By: Relevance
“…However, it should be noted that Vif potently inhibits the encapsidation of A3G by HIV-1 (20 -24), which should completely disrupt this competition. On the other hand, it has been reported that A3G binds to MOV10 (25)(26)(27). Thus, even when the neutralization of A3G by Vif is incomplete, remnant A3G proteins may enhance MOV10 packaging as long as the domain on A3G that binds to MOV10 does not overlap with the domain that binds to NC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that Vif potently inhibits the encapsidation of A3G by HIV-1 (20 -24), which should completely disrupt this competition. On the other hand, it has been reported that A3G binds to MOV10 (25)(26)(27). Thus, even when the neutralization of A3G by Vif is incomplete, remnant A3G proteins may enhance MOV10 packaging as long as the domain on A3G that binds to MOV10 does not overlap with the domain that binds to NC.…”
Section: Discussionmentioning
confidence: 99%
“…The identity of the RNA(s) that promote A3G packaging in HIV-1 infected cells remains somewhat unresolved, though HIV-1 genomic RNA and 7SL RNA (a small pol III transcript that is found in the signal recognition particle, SRP) have each been assigned stimulatory roles in the process (Luo et al 2004;Khan et al 2005Khan et al , 2007Wang et al 2007). The fact that A3G is an avid RNA-binding protein ( Navarro et al 2005;Iwatani et al 2006) raises an important question concerning packaging: specifically, since A3G is associated with an array of cellular ribonucleoprotein (RNP) complexes in an RNA-dependent manner (Chiu et al 2005(Chiu et al , 2006Chelico et al 2006;Kozak et al 2006;Wichroski et al 2006;Gallois-Montbrun et al 2007), how can its RNA-binding site(s) be liberated to allow engagement with the RNA that facilitates packaging? Accordingly, elegant pulse-chase analyses revealed that it is newly synthesized A3G that is incorporated into virions, presumably averting its recruitment into cytosolic RNPs (Soros et al 2007).…”
Section: The Packaging Of Apobec3g Into Hiv-1 Virionsmentioning
confidence: 99%
“…An association of A3G with exogenously expressed components of stress granules (SGs) and processing bodies (PBs) has been reported (Kozak et al 2006;Wichroski et al 2006;Gallois-Montbrun et al 2007). The fact that Staufen RNA granules, SGs and PBs represent a continuum of granular-like structures in which cargos may be transferred back and forth could contribute to these results.…”
Section: Rnp Complexes In Hmm A3g Complex Assemblymentioning
confidence: 99%
“…Numerous cellular RNA-binding proteins with diverse roles in RNA function, metabolism and fate determination are found in these HMM A3G complexes, and their participation in the complex occurs in an RNAdependent manner (Chiu et al 2006;Kozak et al 2006;Gallois-Montbrun et al 2007). Careful analysis suggests that these components fall into at least three previously defined multi-subunit RNP complexes in human cells: (i) Staufen-containing, polysome-associated RNA granules, (ii) Ro RNPs, and (iii) select components of prespliceosomes plus reservoirs for transcriptional regulators (Chiu et al 2006).…”
Section: Rnp Complexes In Hmm A3g Complex Assemblymentioning
confidence: 99%
See 1 more Smart Citation